Analisis Financial Technology (Fintech) & Digital Marketing Pada BSI KCP Lumajang S Parman - Sakdia, Halimatus; Suleiman, Yasir (Finance : Journal of Accounting and Finance, 2024)
The development of Financial Technology  in Indonesia has recently been very rapid. This has changed people's lifestyles in various sectors, one of which is the financial sector which has an impact on financial services institutions in the banking sector. Financial Technology is a new technology and innovation that aims to compete with traditional financial methods in delivering financial services, in which there are new applications, processes, products or models that aim to make it easier for society. This financial technology has its own opportunities and challenges to achieve goals from both the bank and customer sides. This research aims to find out the fintech used at BSI KCP Lumajang S Parman, and how digital marketing developments at BSI Lumajang S Parman have increased customers.To identify these problems, this study uses a type of qualitative research. The data collection techniques were carried out using previous research reports, observations, interviews, and documentation. Based on the research that has been done, this research shows that 1) the fintech used at BSI KCP Lumajang S Parman is BSI Mobile and BSI Net which contain various features that make it easy to make transactions. 2) Digital marketing used at BSI KCP Lumajang S Parman namely Whatsapp and Email.